Accessibility, Disability and Deaf: a Review - Soosay Nathan, Shelena; Berahim, Mazniha; Ramle, Rosni; Hussain, Azham; Laily Hashim, Nor; Qurat-Ul-Ain, Ansa (International Journal of Engineering and Technology, 2018)
Usability is an important attribute that needs more concentration in determining the production of a successful mobile application. Currently, deaf people has increased using mobile and the application tremendously. However, accessibility being under measured as many disability applications are being left unused after quite some time. To better suit the need of mobile applicationsfor the disability people, the level of accessibility needs to be measured accordingly. This study uses Systematic Literature Review (SLR) to review accessibility needs for a disability people application especially deaf people mobile application. Result from SLR shows that accessibility for mobile application for the deaf are measured limited in terms of its usage among deaf people due to lesser appropriate needs incorporated. This study helps mobile developers and evaluators in evaluating mobile application for the deaf by ensuring the accessibility are measured accordingly.
Keywords: accessibility; deaf; disability; usability; mobile applications; evaluation